2016
DOI: 10.3892/or.2016.4637
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of liver cancer-associated stellate cell-induced stem-like characteristics in SMMC-7721 cells by 8-bromo-7-methoxychrysin via inhibiting STAT3 activation

Abstract: Hepatic stellate cells (HSCs) that are activated by human hepatocellular carcinoma (HCC) cells secrete a variety of cytokines, which are the main component of the HCC microenvironment. We aimed to determine whether 8-bromo-7-methoxychrysin (BrMC) could interfere in cross-talk of the human hepatic stellate cell line LX-2 and liver cancer stem-like cells (LCSLCs) to inhibit the characteristics of LCSLCs endowed with the capacity of sustaining human hepatocellular carcinoma (HCC) self-renewal and progression, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“… 17 Studies also showed that FoxM1 upregulated by MnSOD overexpressionis associated with stemness in CSLCs. 17 , 29 , 31 34 Consistent with these results, the present study found that change of MnSOD expression markedly affected FoxM1 expression, whereas FoxM1 level change did not alter MnSOD expression. In addition, overexpression of FoxM1 reversed the inhibitory effects of MnSOD silencing on migratory and invasive abilities and EMT in MHCC97H cells.…”
Section: Discussionsupporting
confidence: 90%
“… 17 Studies also showed that FoxM1 upregulated by MnSOD overexpressionis associated with stemness in CSLCs. 17 , 29 , 31 34 Consistent with these results, the present study found that change of MnSOD expression markedly affected FoxM1 expression, whereas FoxM1 level change did not alter MnSOD expression. In addition, overexpression of FoxM1 reversed the inhibitory effects of MnSOD silencing on migratory and invasive abilities and EMT in MHCC97H cells.…”
Section: Discussionsupporting
confidence: 90%
“…Fibroblasts and MSCs co-cultured directly with tumor cell lines show marked up-regulation of FAP( 56 , 57 ), but no-contact co-culture with adenoma explants could also induce FAP expression by bone-marrow MSCs (BM-MSCs)( 15 ), as could conditioned media from myeloma cells( 57 , 58 ). Additionally, conditioned media from liver cancer cells enhanced FAP expression on umbilical cord MSCs( 59 ) and hepatic stellate cells( 60 ), the latter in a STAT3- dependent manner. Various factors may be implicated in tumor-mediated up-regulation of FAP.…”
Section: Molecular Biology Of Fapmentioning
confidence: 99%
“…In cancer, these cells share many of the same functions as CAFs at the level of the CSC niche. It has been reported that HSCs secrete HGF or IL-6 that induce the expression of stemness markers in CSCs, and this increased expression is mediated through STAT3 signaling [218,219]. The investigation of the crosstalk between HSCs and CSCs resulted in the identification of the transcription factor Forkhead Box M1 (FOXM1) as a main player in HSC activation and maintenance of stemness in CSCs in vitro.…”
Section: The Csc Niche In Hcc: Ectopic Lymphoid Structures and Hepatimentioning
confidence: 99%